Moving away from gender blind tools: Engendering the livestock feed assessment tool - Lukuyu, Ben A. (International Livestock Research Institute, 2016)
The “FEAST” livestock feed-assessment tool has been widely promoted and adopted, but as time passed the research team started receiving feedback. They were told that the tool was gender-blind. So the researchers adapted the tool to measure gender-related issues. Pretesting showed that the tool had missed a lot of important information – on roles, problems, preferences, etc. The team also reviewed the process of gathering data and checking its accuracy (for example, making separate groups of men and women). The tool has improved tremendously, but it now takes double the time to apply. The researchers want to keep the tool acceptable and popular while making it better at reflecting gender realities. Interview with Ben Lukuyu (ILRI) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684